A PROSPECTIVE CLINICAL STUDY ON DISEASE KNOWLEDGE AND MEDICATION ADHERENCE PATTERN AMONG ASTHMATIC PATIENTS IN TERTIARY CARE HOSPITAL IN A TIRUPUR POPULATION - A, Muthukumar; Ganapathy R, Sundara (Asian Journal of Pharmaceutical and Clinical Research, 2017)
Objectives: To study the disease knowledge and drug adherence among asthmatic patients in tertiary care hospital in a rural population. Methods: A total of 99 patients with bronchial asthma study conducted in tertiary care hospital in rural population face to face interaction with patients follow-up have done for 4 months. This clinical study was administered with standard questionnaires evaluating the patient knowledge and medication adherence (MA) Morisky8-items MA scale toward asthma and treatment. Results: A total of 99 patients were evaluated for this clinical study. 43.5% of the patients were male and 56.4% were female. The percentage of the mean score of knowledge and MA are 17% and 18%, with their standard deviation of 1.51 and 1.64, respectively. Conclusion: This study demonstrated that the patient's specific knowledge regarding asthma was low. However, few patient's had favorable attitude toward their disease, but other did not have the necessary knowledge of disease management. In addition, the drug adherence was also poor in occupation induced asthmatics patients.